PENGARUH PENERAPAN PENDEKATAN RME TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP - Melvi Khairani; Hari Sumardi; Effie Efrida Muchlis (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The ability to answer mathematical issues gave pupils the chance to use it to overcome obstacles in everyday life as well as in the fields of mathematics and other sciences. A method known as Realistic Mathematics Education (RME) connected mathematical difficulties to pertinent real-world concerns. The purpose of this study was to ascertain whether the RME approach had an impact on the eighth-grade students at SMP Negeri 03 in Bengkulu City's capacity to solve mathematical problems. A quasi-experimental design with a nonequivalent control group was the study methodology employed. The treatment (X) or learning with the RME approach was applied to the first group, while the other group received conventional learning or no treatment. The sample was chosen using the purposive sampling technique. The study's findings demonstrated that the use of the RME approach affected the students' capacity to solve mathematical problems, as evidenced by a sig. (2-tailed) value of 0.001 significance level (α) = 0.05 based on the independent sample t-test statistical test on the two sample classes. Additionally, the average N-Gain score obtained was 0.40, which was classified as a "moderate" increase in understanding. Thus, it could be concluded that the use of the RME approach had a positive impact on the improvement of students' mathematical problem-solving abilities.